Three-dimensional Numerical Study of the Seismic Response of Piled Raft using Pseudo-static Method (Latakia University Journal -Engineering Sciences Series, 2024)
A piled raft foundation (PRF) is generally used for high-rise buildings, the conventional design of piled raft does not include the capacity of piled raft under combined lateral and vertical load, however vertical (v), horizontal (H)loading may act on the foundation simultaneously. The present study examines the behavior of piled raft foundation in sandy soil under V-H(Pseudo-static) interaction using plaxis3D.We study the effect of these force on bearing capacity of the raft and the horizontal displacement through a parametric study of the most important influencing factors (internal friction angle Φ, relative density of sand D, the length to width ratio L/B, effect the spacing to diameter ratio of pile S/D,  thickness of the raft,  effect the pile position and distributing of pile in different methods).The results of the numerical study show that the capacity of piled raft increases with increase in the relative density of the sand, and the optimal thickness of the raft was 1m, we found that the front row of pile takes larger shear of the lateral load compared to the successive rows.the present results are useful because they provide a broader understanding of the response of PRF under vertical and horizontal loading conditions.